Race specific nomograms: time for change? - Varughese, Pearl Mary; Rajan, Nishanth; Mani, Manikandan; Krishnan, Lalitha (International Journal of Contemporary Pediatrics, 2018)
Background: Hyperbilirubinemia is a common problem in neonates. Because of the genetic differences in bilirubin metabolism, an hour specific nomogram is better in each geographical location. No studies in South India for creation and validation of a nomogram for significant hyperbilirubinemia. The aim of this study was to create and validate a bilirubin nomogram in South Indian infants. Methods: A prospective cross-sectional study. The data was collected in 2 parts, over 18 months (264 infants) and 20 months (450 infants) respectively. Babies with established direct hyperbilirubinemia, polycythemia, hypothyroidism, culture proven sepsis, major congenital anomalies and jaundice on day 1 of life were excluded. For all babies, cord bilirubin (for first set of infants), total serum bilirubin values were sent at 24 hours of life and at the time of discharge. An hour specific nomogram was created with 834 bilirubin values (first set of data). The predictive ability of this nomogram and Bhutani nomogram were tested and compared using 972 total serum bilirubin values (second set of data) Results: A nomogram was created with serum bilirubin values from the first set of infants and validated it with the serum bilirubin values from the second set of infants. Bhutani nomogram was also validated. Comparing with Bhutani nomogram, our nomogram was better in predicting significant hyperbilirubinemia in our population. Conclusions: Discharging neonates without risk assessment for severe hyperbilirubinemia may be dangerous. A nomogram generated and validated with our data is an accurate tool for predicting significant hyperbilirubinemia in our population.